2009
DOI: 10.1007/s11274-009-0181-5
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous yeast communities in the environment of “Rovello bianco” grape variety and their use in commercial white wine fermentation

Abstract: The indigenous yeast communities associated with several vineyard habitats were analysed. Wild yeasts were isolated, differentiated at strain level and identified. A phylogenetic tree based on partial 26S rRNA genes was constructed. The strains were characterized and the indigenous Saccharomyces cerevisiae GR1 was then used to carry out a vinification process and compared with a commercial yeast. Wines obtained were subjected to chemical and sensory analysis. The comparison between the two products highlighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 42 publications
(38 reference statements)
2
40
1
Order By: Relevance
“…From our practical observations some Saccharomyces strains may develop colonies on this medium. R. glutinis, a species found associated to several fermented foods (Arroyo-López et al, 2008;Francesca et al, 2010), was revealed at subdominant levels in this work.…”
Section: Discussionmentioning
confidence: 57%
“…From our practical observations some Saccharomyces strains may develop colonies on this medium. R. glutinis, a species found associated to several fermented foods (Arroyo-López et al, 2008;Francesca et al, 2010), was revealed at subdominant levels in this work.…”
Section: Discussionmentioning
confidence: 57%
“…Chemical measurements (Table 2) were performed as reported by Francesca et al (2010). Glycerol, malic and lactic acid contents were determined by means of enzymatic kits (R-Biofarm, Darmstadt, Germany).…”
Section: Chemical Analysismentioning
confidence: 99%
“…The flavours and chemical composition of wine are usually related to the general environmental conditions insisting on vineyards from which wine is produced [2] Many geographical factors such as climate, soil geology and composition, wild yeasts [3,4] and lactic acid bacteria [5], are able to synergistically influence wine molecular characteristics [6]. The relationship between wine quality and its specific site of production is commonly described by the French term "terroir" [7].…”
Section: Introductionmentioning
confidence: 99%